Viruses Special Issue “Transfusion-Transmitted Viral Infections” - Candotti, Daniel (Viruses, 2022)
Blood transfusion is a life-saving treatment that requires patients to have access to safe and adequate blood products that are available in a timely manner [...].Blood transfusion is a life-saving treatment that requires patients to have access to safe and adequate blood products that are available in a timely manner [...].